Flapless Surgical Approach to Extract Impacted Inferior Third Molars: A Retrospective Clinical Study - Alberto Materni (Journal of Clinical Medicine, 2021)
This study aimed to compare a flapless surgical approach (FSA) with a traditional envelope flap (traditional approach (TA)). Every patient was treated with two approaches: TA and FSA. The primary outcome variables were both the discomfort during the post-operative convalescence and the correct final recovery of the impacted area. The secondary outcome variable was the average duration of the surgery. Post-operative pain and oedema were recorded. The measurements of soft tissue interface toward the distobuccal edge of the second molar were taken by periodontal probe before surgery (baseline) and 8 weeks after surgery. Statistical software was used to evaluate the data; a p-value < 0.05 was considered statistically significant. Twenty-four teeth of 12 patients (six Caucasian males and six Caucasian females, aged 23 ± 4 (17–30) years) with both lower impacted third molars (Ms3) were analysed. Considering an alpha error 0.05 that sample size allows power from 0.80 to 0.90, depending on the variable evaluated. Concerning attached gingiva, oedema and pain, the linear mixed model resulted in a statistically significant difference between the TA and FSA (p = 0.003; p < 0.01; and p = 0.018, respectively). Conversely, the model did not show a difference (p = 0.322) if pocket probing depth was considered. The FSA procedure was faster (p < 0.05) than the TA procedure (17 min and 8 s (± 6 s) vs. 28 min and 6 s (± 4 s), respectively). The results suggest that the FSA could be a suitable option for improving the surgical removal of lower Ms3. However, additional randomized controlled trial studies are necessary to confirm the reliability of our procedure and to verify its suitability in more complex Ms3 classifications.